The administrative processes of pedagogy and the socio-cultural aspects of inclusion and techno-pedagogy through the pedagogical trends on distance and virtual Education - Torres-Ortiz, Jaime Andrés; Duarte, Julio Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This research focuses on the study and analysis of the state of art of teaching trends in Virtual and Distance Education as a part of a doctoral thesis. The findings presented in this study show pedagogical trends which are integrated into administrative processes of pedagogy like techno-pedagogy, digital pedagogy and traditional processes of behavioral trends: conductism, cognitivism, constructivism and humanistic pedagogy. All of these trends are located in different educational contexts with their own particularities of the technological and communicational mediations. In the same way, the cognitive and pedagogical constructivism trends are observed where autonomous learning is the most important characteristic of Virtual and Distance Education, being all of these integrated to instructional pedagogies, constructivism and humanistic pedagogy as a part of the guidelines of the Educational Quality in this modality.